ChemInform Abstract: Synthetic Studies on the Role of Substituents at C‐3 Position on C3—C4 Bond Cleavage of β‐Lactam Ring: Convenient Route for Diastereoselective Synthesis of Pyridin‐2‐ones. Issue 18 (11th April 2013) - Singh, Pardeep; Singh, Parvesh; Kumar, Kewal; Kumar, Vipan; Mahajan, Mohinder P.; Bisetty, Krishna
Abstract The effect of various electron withdrawing as well as electron donating substituents on the C3‐position on the C3/C4 bond cleavage is studied.